Key to Chinese species of the leafhopper genus Drabescus (Hemiptera: Cicadellidae: Deltocephalinae) with description of a new species - Shang, Suqin; Webb, M. D.; Zhang, Yalin (Zootaxa, 2014)
A new species, Drabescus quadrispinosus sp. nov., is described and illustrated. A checklist to the Chinese species of Drabescus is given and a key provided for identification of males. Specimens tentatively identified as D. ineffectus (Walker) from China are discussed and figured.